Imaging nano-objects by linear and nonlinear optical absorption microscopies. (4th September 2015) - Devadas, Mary Sajini; Devkota, Tuphan; Johns, Paul; Li, Zhongming; Lo, Shun Shang; Yu, Kuai; Huang, Libai; Hartland, Gregory V
Abstract Absorption based microscopy measurements are emerging as important tools for studying nanomaterials. This review discusses the three most common techniques for performing these experiments: transient absorption microscopy, photothermal heterodyne imaging, and spatial modulation spectroscopy. The focus is on the application of these techniques to imaging and detection, using examples taken from the authors' laboratory. The advantages and disadvantages of the three methods are discussed, with an emphasis on the unique information that can be obtained from these experiments, in comparison to conventional emission or scattering based microscopy experiments.